Pengaruh Konseling Eksistensial Humanistik Konseling terhadap Pemahaman Pilihan Karir Siswa - Widya Rayi Pangestika; Raudah Zaimah Dalimunthe; Alfiandy Warih Handoyo (STIKes Ibnu Sina Ajibarang, 2025)
The research aims to see the influence of humanistic existential counseling. The method used in this research uses experimental research methods. The research was carried out at SMA Negeri 3 Cibinong in the Odd Semester of the 2024/2025 academic year. Based on the results of the pre-test conducted on class , and 110 students are in the “Very High” category. It can be concluded that the level of understanding of career choices of SMA Negeri 3 Cibinong students is in the very low, low, high and very high categories. From the results of the pre-test, the researcher took 8 students as research subjects. The eight students will be united into 1 counseling group in experimental research which will be given treatment in eight meeting sessions using career counseling with an existential humanistic counseling approach.